2019
DOI: 10.1063/1.5116625
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced self-bias magnetoelectric effect in locally heat-treated ME laminated composite

Abstract: This study reports the improvement in the magnetoelectric (ME) coupling effect in a locally heat-treated FeBSi (Metglas)/Pb(Mg1/3Nb2/3)O3-PbZrO3-PbTiO3 single crystal laminated composite under zero magnetic bias. The high-temperature pulse laser treatment could induce local crystallization along the laser scanning line, but adjacent domains remained still amorphous, which resulted in the thermal and lattice mismatch. Therefore, it could produce a residual stress between the crystalline and amorphous phases, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
9
1
1
Order By: Relevance
“…Correspondingly, the LoD was enhanced by almost an order of magnitude approaching 400 fT/Hz 1/2 at the electromechanical resonance, as shown in Figure 6b [47]. Based on the giant resonance ME coupling coefficient in 1-1 type ME laminate, a superhigh resonant magnetic-field sensitivity close to be 135 fT (see Figure 6c) was further obtained by Chu et al [8], which indicates great potential for 1-1 type ME composites in the field of eddy current sensing, space magnetic sensing and active magnetic localizing [8,62]. In 2018 Turutin et al reported a new ME composite consisting of the y + 140 • cut congruent lithium niobate piezoelectric plates with an antiparallel polarized "head-to-head" bidomain structure and magnetostrictive material Metglas [48].…”
Section: Resonant-frequency Magnetic Sensormentioning
confidence: 81%
“…Correspondingly, the LoD was enhanced by almost an order of magnitude approaching 400 fT/Hz 1/2 at the electromechanical resonance, as shown in Figure 6b [47]. Based on the giant resonance ME coupling coefficient in 1-1 type ME laminate, a superhigh resonant magnetic-field sensitivity close to be 135 fT (see Figure 6c) was further obtained by Chu et al [8], which indicates great potential for 1-1 type ME composites in the field of eddy current sensing, space magnetic sensing and active magnetic localizing [8,62]. In 2018 Turutin et al reported a new ME composite consisting of the y + 140 • cut congruent lithium niobate piezoelectric plates with an antiparallel polarized "head-to-head" bidomain structure and magnetostrictive material Metglas [48].…”
Section: Resonant-frequency Magnetic Sensormentioning
confidence: 81%
“…Magnetic bias originates from the exchange coupling interaction between ferromagnetic layers and antiferromagnetic layers (antiferromagnetic spins induce ferromagnetic spins via an interface coupling to generate microtorques and interface orbital reconstruction, resulting in an exchange bias response) 62,63 or soft and hard two-phase magnetic exchange bias (localized unidirectional stray fields generated by uncompensated poles of hard particles/ shells in soft amorphous matrix/core). 64,65 The change in the magnetization state due to the exchange bias effect provides an intrinsic bias magnetic field to the SME materials, resulting in the translation of the M-H hysteresis loop or the magnetostriction curve (λ and q = δλ/dH) of the ferromagnetic phase. The exchange bias behavior is usually manifested as a horizontal displacement of the hysteresis loop along the magnetic field direction (axis), namely, the exchange bias field, which depends on the thickness of the multicomponent magnetic system, the interface microstructure, and the magnetic field direction (dip angle).…”
Section: Exchange Bias Effectmentioning
confidence: 99%
“…119 S. Dong's group further explored the ME coupling effect of locally heat-treated Metglas/PMN-PT singlecrystal laminate composites. 65,120 The stress effect of the crystallinity and amorphous interface on the ME coupling was analyzed. High-temperature pulsed laser heat treatment induced the local crystallization of Metglas along the laser direction, while the adjacent magnetic domains remained amorphous.…”
Section: Metglasmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method of shifting the magnetostrictive coefficient to the working point is the use of additional magnetic layers that affect the magnetostrictive phase due to their own remanence magnetization. Local laser heating of the magnetostrictive layer (Metglas) was used for forming a surface layer with a recrystallized material containing the α-Fe phase [10]. This phase after placing it in a DC magnetic field retains remanence magnetization, which can affect the more magnetically soft metglas, and therefore generate a non-zero ME coefficient in the absence of an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%